2017
DOI: 10.17356/ieejsp.v3i4.412
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Operational Representations

Abstract: Since 2011, the EU has called upon its member states to step up their efforts to improve the socioeconomic conditions facing many Roma. It has also sought to secure the ethnic representation of the Roma in these efforts. By doing so, the EU has tried to strike a balance between redistribution and recognition: it has recognized the ethnic specificity of this group, but it has also framed the issue as one that requires a socioeconomic solution. Using insights from frame analysis, visual theory and governmentalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…First, our results revealed that the dominant social structure maintained a discriminatory and oppressive role, causing health inequities and silencing the voices of the Roma community. Accordingly, traditional approaches to health governance use processes that control and co-opt Roma voices, or what the agents identified as being "silenced" and "not represented" (Baez-Camargo, 2020; Vermeersch & Van Baar, 2017). Meaningful community advocacy promotes multiple voices and legitimatizes the narratives of Roma people highlighting what works, for whom, and in what circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…First, our results revealed that the dominant social structure maintained a discriminatory and oppressive role, causing health inequities and silencing the voices of the Roma community. Accordingly, traditional approaches to health governance use processes that control and co-opt Roma voices, or what the agents identified as being "silenced" and "not represented" (Baez-Camargo, 2020; Vermeersch & Van Baar, 2017). Meaningful community advocacy promotes multiple voices and legitimatizes the narratives of Roma people highlighting what works, for whom, and in what circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The question of who counts as Roma (Surdu, 2016) is a complex and politicised one in the Swedish context, as in much of Europe (McGarry, 2014;Vermeersch, 2012;Vermeersch & van Baar, 2017). It is a question that has significant socio-political implications: It is central to the contemporary politics of recognition, historical justice, minority rights protection, and socio-economic integration.…”
Section: 'Who Counts As Roma?'mentioning
confidence: 99%